2015
DOI: 10.1002/chem.201503314
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Carbonylative Cyclization of Arenes by CH Bond Activation with DMF as the Carbonyl Source

Abstract: A novel palladium-catalyzed CO-gas- and autoclave-free protocol for the synthesis of 11H-pyrido[2,1-b]quinazolin-11-ones has been developed. Quinazolinones, which are omnipresent motif in many pharmaceuticals and agrochemicals, were prepared in good yields by C-H bond activation and annulation using DMF as the CO surrogate. A (13) CO-labelled DMF control experiment demonstrated that CO gas was released from the carbonyl of DMF with acid as the promotor. The kinetic isotope effect (KIE) value indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 69 publications
(20 reference statements)
1
30
0
1
Order By: Relevance
“… 2 6 In the past decades, N-monosubstituted secondary (2° amine) anilines and alkynes have been extensively used in this field with the assistance of stoichiometric oxidants in most cases (i, Scheme 1a ). 3 , 4 However, despite this significance, the preparation of 2° anilines often requires tedious multi-steps because the tertiary (3°) amines would be mainly obtained by a traditional substitution reaction. In addition, the difficulty in removing the R group from the formed N-heterocycles also limits their further transformation.…”
Section: Introductionmentioning
confidence: 99%
“… 2 6 In the past decades, N-monosubstituted secondary (2° amine) anilines and alkynes have been extensively used in this field with the assistance of stoichiometric oxidants in most cases (i, Scheme 1a ). 3 , 4 However, despite this significance, the preparation of 2° anilines often requires tedious multi-steps because the tertiary (3°) amines would be mainly obtained by a traditional substitution reaction. In addition, the difficulty in removing the R group from the formed N-heterocycles also limits their further transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its cheapness and easy accessibility, among the possible candidates, DMF represents an attractive CO source . In 2015, Wo and co‐workers developed a palladium‐catalyzed carbonylative cyclization of N ‐arylpyridin‐2‐amines 97 by C–H activation using DMF (Scheme ) . The best carbonylation conditions of both electron‐rich and ‐poor substrates 97 , leading to the corresponding quinazolinone derivatives 98 , were achieved with DMF in the presence of Pd(OAc) 2 as catalyst, using K 2 S 2 O 8 as oxidant, TFA as co‐solvent at 140 °C under oxygen atmosphere (Scheme ).…”
Section: Alternative Sources Of Carbon Monoxide In the Pd‐catalyzementioning
confidence: 99%
“…The best carbonylation conditions of both electron‐rich and ‐poor substrates 97 , leading to the corresponding quinazolinone derivatives 98 , were achieved with DMF in the presence of Pd(OAc) 2 as catalyst, using K 2 S 2 O 8 as oxidant, TFA as co‐solvent at 140 °C under oxygen atmosphere (Scheme ). Moreover, 13 CO‐labelled DMF studies have shown that the carbonyl group of DMF is the CO source which releases carbon monoxide in situ at elevated temperature with the aid of an acid …”
Section: Alternative Sources Of Carbon Monoxide In the Pd‐catalyzementioning
confidence: 99%
“…DMF is an attractive CO‐surrogate because of the low price and commercial availability. The decarbonylation of DMF has previously been studied by the groups of Hallberg et al, Chang et al, Bhanage et al, and Nozaki et al More recently, Wu and coworkers demonstrated that 13 C‐labeled DMF could be decarbonylated under acidic conditions to liberate [ 13 C ]CO, which could subsequently be used in two similar Pd‐catalyzed oxidative carbonylation reactions affording a 13 C‐labeled quinazolinone ( 101 ; Scheme ).…”
Section: C‐carbonylation Using [13c]comentioning
confidence: 99%